An examination of the steady‐state assumption in soil development models with application to landscape evolution. Issue 15 (30th August 2017) - Yu, F.; Hunt, A.G.
Abstract: Soil depth and soil production are highly complicated phenomena, generated from a complex interaction of physical, biological and chemical processes. It has, nevertheless, become increasingly clear that soil formation rates are closely related to chemical weathering rates. Somewhat paradoxically, it is likewise becoming apparent that such biogeochemical reactions as slowly transform rock to soil are limited by physical processes, such as flowing water and the formation of fractures. We have formulated a theoretical approach that relates soil formation rates to chemical weathering rates, and those, likewise, to solute transport rates. For such a theoretical framework to be relevant, the solute transport rates cannot equal those of the flowing water, as is the case in Gaussian solute transport. Rather, solute transport must be slowed in accordance with heavy‐tailed solute arrival time distributions. The inference is that the traditional advection–dispersion equation formulation for solute transport is inadequate in the typically heterogeneous geological media that weather to form soils. Here we examine the implications of this soil production model on the assumption of the approach to steady state. Particularly at slow erosion rates we find that many soil columns are not in equilibrium. This tendency may be accentuated in dry climates. Copyright © 2017 John Wiley & Sons, Ltd. Abstract : Predicted steady‐state soil depths, a negative power of the erosion rate, continue to rise with diminishing erosion rates. Field data, however, indicate a tendency for soil depths at low erosion rates to converge to about 1 m. In our theory, the discrepancy is due to the very large time scales required for equilibrating soil production and soil erosion at very low erosion rates. Correcting for non‐steady‐state conditions at finite times, as shown here, eliminates the discrepancy.